Hubungan Tingkat Pengetahuan, Sikap Siswa SMAN Se- Kota Pekanbaru Terhadap Praktik Penggunaan Obat Analgetik Yang Dijual Bebas Di Pasaran - Ayu Rahmawati; Nursyafni; Nurhasanah; Efilia Meirita (LPPM, Universitas Muhammadiyah Riau, 2024)
Analgesics are drugs that are often used to relieve pain without affecting a person's consciousness. This study aims to determine the relationship between the level of knowledge, attitudes of SMAN students in Pekanbaru City towards the practice of using analgesic drugs sold over the counter on the market. This study uses a descriptive survey method with a sampling technique, namely the simple random sampling technique using a questionnaire instrument. Where there were 367 respondents involved in this study, dominated by 204 females and 163 male respondents. The age range is 15-18 years, the majority of whom are 16 years old. Data analysis using bivariate using chi square test and multivariate using F test. The results showed that the level ofknowledge was sufficient 251 respondents (68.4%), positive attitude 311 (84.7%) and lack of practice as many as 276 (75.2%). In bivariate analysis there was a significant relationship between knowledge of the practice of using analgesic drugs with (p value = 0.000 <0.05). There was no significant relationship between attitudes towards the practice of using analgesic drugs with (p value = 0.0716 > 0.05). This study emphasizes the importance of education about the use of analgesic drugs among high school students to prevent drug abuse